18F-FDG PET/CT in Late Acquisition Identifies Sites of Active Disease in Treated Takayasu Arteritis. Issue 1 (January 2022) - de Souza Santos, Marília Paula; Ramos, Celso Dario; Paixão, Mariana; Pignaton Naseri, Estephania; Barros Bertolo, Manoel; Sachetto, Zoraida
Abstract : Objective: Few studies have taken advantage of 18 F-fluorodeoxyglucose positron emission tomography associated with computed tomography ( 18 F-FDG PET/CT) to personalize patient evaluation and identify sites of more active disease in Takayasu arteritis (TA)–treated patients. This study aimed to evaluate the utility of 18 F-FDG PET/CT in late acquisition in identifying sites of active disease in patients under full treatment for TA. Methods: In this cross-sectional study, patients under full treatment underwent whole-body 18 F-FDG PET/CT. Sites of increased 18 F-FDG uptake were classified by a score of 3 on the visual scale using the liver uptake as reference. A quantitative analysis was also performed by measuring the maximum standardized uptake value (SUV) of the vascular wall of affected arteries. Disease activity using the National Institutes of Health criteria was also evaluated. Results: Of the 20 patients, there were 18 female and 2 male patients, with a mean age of 43.6 (±11.58) years and a disease duration of 8.3 (±6.25) years. Thirteen participants (65%) were in inflammatory activity according to the criteria proposed by the National Institutes of Health. All patients received immunosuppressive agents, and one of them received immunobiological treatment. The highest SUV value was 6.2 in the aortic arch, and the lowest was 1.0 in the subclavian artery. The mean maximum SUV did not differ between clinically active and inactive patients. In the visual analysis, all participants had at least 1 vascular site with inflammatory activity, with an uptake ≥2 in relation to the liver. The aortic arch was the most frequently involved site. Conclusions: This study showed that 18 F-FDG PET/CT in late acquisition is an effective imaging method to assess TA activity even in fully treated patients.